Salivary pH, dental caries and Body Mass Index (BMI) in the middle school students in Eastern Makassar - Rafikah Hasyim; Dwi P. Wulansari; Karima Q. Mansjur; Nasyrah Hidayati (Journal of Dentomaxillofacial Science, 2021)
Objective: This study aimed to assess the association of salivary pH, dental caries and body mass index (BMI) in middle school students in eastern MakassarMaterial and Methods: This study included 60 middle school students from two schools in eastern Makassar. Data were collected by filling out a questionnaire, weight and height measurement, dental examination, and saliva collection. Body mass index was calculated by dividing weight and height in kg/m2, saliva was collected by draining method, and salivary pH was measured with Saliva-Check Buffer (GC Japan). Decay Missing Filled-Teeth (DMF-T) indexes are used to assess dental caries. Statistical analysis was performed by chi-square and ANOVA with a significance of 0.05.Results: This study showed that overweight and obesity are more prevalent in female students than male students. Salivary pH in underweight students and overweight and obese students were lower compared to normal BMI students, while DMF-T score in underweight, overweight, and obese students were higher than the normal BMI students.Conclusion: It can be concluded that BMI have a significant association with salivary pH and DMF-T score.1.       Wang L, Zhou B, Zhao Z, et al. Body-mass index and obesity in urban and rural China: findings from consecutive nationally representative surveys during 2004–18. Lancet 2021;398: 53-63.2.       Garrouste-Orgeas M, Troché G, Azoulay E, et al. Body mass index. Intensive Care Med 2004;30: 437-443.3.       Barlian B, Azhari, Pramanik F. Correlation between mandibular trabeculae bone density on panoramic radiograph and body mass index of men aged 5-35 years old. J Dentomaxillofac Sci 2018;3: 166-168.4.       Bellagambi FG, Lomonaco T, Salvo P, et al. Saliva sampling: Methods and devices. An overview. TrAC-Trends Anal Chem 2020;124: 115781.5.       Zalewska A, Kossakowska A, Taranta-Janusz K,et al. Dysfunction of salivary glands, disturbances in salivary antioxidants and increased oxidative damage in saliva of overweight and obese adolescents. J Clin Med 2020;9: 548.6.       Mosca AC, Stieger M, Neyraud E, et al. How are macronutrient intake, BMI, ethnicity, age, and gender related to the composition of unstimulated saliva? A case study. J Texture Stud 2019;50: 53-61.7.       Pannunzio E, Amancio OMS, Vitalle MSDS, et al. Analysis of the stimulated whole saliva in overweight and obese school children. Rev Assoc Méd Bras 2010;56: 32-36.8.       Primasari A, Hulu KP. Dryness of the oral cavity in the salivary status of overweight women. J Homeop Nat Med 2019;5: 50-53.9.       Al-Hussaini A, Bashir MS, Khormi M, et al. Overweight and obesity among Saudi children and adolescents: Where do we stand today?. Saudi J Gastroenterol 2019;25: 229.10.    Hruby A, Hu FB. The epidemiology of obesity: A big picture. Pharmaco Economics 2015;33: 673-689. 11.    Alshihri AA, Rogers HJ, Alqahtani MA, et al. Association between dental caries and obesity in children and young people: A Narrative Review. Int J Dent 2019;2019: 1-8. 12.    Groth SW, Morrison-Beedy D. Obesity risk in urban adolescent girls: nutritional intentions and health behavior correlates. J NY State Nurses Assoc 2011;42: 15-28.13.    Baliga S, Muglikar S, Kale R. Salivary pH: A diagnostic biomarker. J Indian Soc Periodontol 2013;17: 461.14.    Anamaria B, Eugen B, Daniela E, et al. Interrelation between salivary pH, buffer capacity and dental caries in underweight, normal weight and overweight children. Revista de Chimie 2017;68: 1353-1356.